Effects of tillage and biochar on soil physiochemical and microbial properties and its linkage with crop yield - Chen, Wenju; Li, Peipei; Li, Fang; Xi, Jingjing; Han, Yanlai (Frontiers in Microbiology, 2022)
Vertisols are clayey soils with a high potential for improving production. Therefore, understanding the impact of tillage and fertilization on soil physicochemical properties and microbial community is essential for improving vertisols with high montmorillonite and smectite clay content. A three-year field experiment was conducted to compare the effects of different tillage and fertilization practices at three depths of the vertisol under the wheat-maize cropping system in the North China Plain. The experiment treatments included rotary tillage without fertilization (R-CK), rotary tillage with chemical nitrogen (N), phosphorus (P), and potassium (K) fertilization (R-NPK), R-NPK plus biochar (R-NPKB), deep tillage without fertilization (D-CK), deep tillage with chemical N, P, and K fertilization (D-NPK), and D-NPK plus biochar (D-NPKB). The results showed that D-NPKB significantly improved winter wheat and summer maize yields by 14.4% and 3.8%, respectively, compared with R-NPK. The nitrate (NO3--N) content of the deeper soil layer in D-NPKB was significantly higher than that in D-NPK. Meanwhile, biochar application increased the pH in the three layers. Compared with R-NPK, D-NPKB significantly increased the average content of available phosphorus (AP), soil organic carbon (SOC), and total nitrogen (TN) by 73.7%, 18.5%, and 19.0%, respectively. Meanwhile, Gaiellalea, Sphingomonadaceae, and Nocardioidaceae were the predominant bacteria at the family level across all treatments, with a total relative proportion ranging from 14.1% to 23.6%. In addition, the abundance of Bacillaceae in deep tillage was 9.4% higher in the 20–30 cm layer than in rotary tillage. Furthermore, the correlation analysis revealed a significant positive correlation between crop yield and chemical factors such as NO3--N, and the abundances of Gaiellale, Sphingomonadaceae and Nocardioidaceae. The findings collectively indicated that deep tillage combined with biochar application could increase the soil nutrients and modify the bacterial structure in the deeper soil layer and therefore will be beneficial for improving the productivity of vertisols.